L’image politique comme manifeste ? Considérations sur la fresque des saints rois dans l’église (luthérienne) de Mălâncrav (xve siècle) - Doina Elena Craciun (Bulletin du Centre d’Études Médiévales d’Auxerre)
This paper proposes a new interpretation of the fresco illustrating the Holy Kings in the – today lutheran – church of Mălâncrav (Romania), formely situated in the Hungarian Kingdom. The iconographical analysis performed here shows a special interest in depicting an interaction between the figures : the royal saints of the Árpád dynasty and the bishop seem to form a group which faces the royal saint Sigismund. This staging of the two parties seem to mirror the political context during the period when the fresco was made, at the beggining of the 15th century, a time of rebellion of the nobles and ecclesiastical authorities of Hungary against their king, Sigismund of Luxembourg. After analysing the events and the symbols used by the rebels at that time, and considering the fact that the commissioner of the fresco participated at the uprising of 1403, the article proposes to see the figures in the fresco as symbols of the the two rival camps.